2020
DOI: 10.1177/2333794x20982434
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Jaundice: Perception of Pregnant Women Attending Antenatal Clinic at a Tertiary Hospital in Southwest, Nigeria

Abstract: Background: Severe neonatal jaundice (NNJ) remains a leading cause of preventable brain damage, mental handicap, physical disabilities, and early death among infants. Methods: Using a descriptive cross-sectional study design, information was gathered using a structured, pretested questionnaire from 518 pregnant women who attended the antenatal clinic at a tertiary Hospital in Southwest Nigeria. Results: Most (77%) of the respondents have heard about NNJ prior the survey. Most respondents (69.5%) demonstrated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Previous studies on NNJ in Nigeria reported a poor knowledge about its causes, management and complications among pregnant women. [17][18][19][20][21][22] Interestingly in our study, we found less than four antenatal visits as a significant risk factor for neonates to become jaundiced. The risk is 13 times more among cases which indicate the indirect impact of less visits and parental awareness which eventually lead to delay in admission for phototherapy.…”
Section: Resultsmentioning
confidence: 79%
“…Previous studies on NNJ in Nigeria reported a poor knowledge about its causes, management and complications among pregnant women. [17][18][19][20][21][22] Interestingly in our study, we found less than four antenatal visits as a significant risk factor for neonates to become jaundiced. The risk is 13 times more among cases which indicate the indirect impact of less visits and parental awareness which eventually lead to delay in admission for phototherapy.…”
Section: Resultsmentioning
confidence: 79%
“… 13 Furthermore, studies conducted in similar settings (e.g., Nigeria and Ghana) on knowledge, attitudes, and practices toward NH among expectant mothers and caregivers have shown that limited knowledge and poor attitude can lead to delays in seeking care as well as delays in treatment. 14 17 In this study, we evaluated the prevalence of NH in a cohort of in-hospital births in a semi-rural area of Kinshasa (DRC) and the association between NH and neonatal and maternal risk factors. We also investigated expectant mothers’ knowledge and practices regarding this condition.…”
Section: Introductionmentioning
confidence: 99%